Funding Decision Trade Off Theory and Pecking Order Theory Perspectives in Jakarta Islamic Index - Ira Wikartika; Zumrotul Fitriyah; Sonja Andarini; Resa Rasyidah (Nusantara Science and Technology Proceedings)
The operations of the company are always faced with the problem of meeting the needs of funds. Company funding is closely related to the selection and combination of internal funding sources and external funding sources. The funding decision of the capital structure determines the company in carrying out its operating activities that affect the company's value. There are two perspectives in determining the funding decision of capital structure, namely trade-off theory and pecking order theory. This study aimed to analyze the effect of capital structure funding decision variables according to the perspective of trade-off theory and pecking order theory on capital structure funding decision. The study population were companies listed in the Jakarta Islamic Index. There were 30 sample companies used during the period of June to November 2016.The result showed that according to trade-off theory, firm size and growth influenced to leverage, but tangible fixed assets and profitability had no effect on leverage. While according to pecking order theory perspective, it showed that only variable of growth that influenced to leverage. Thus it can be concluded that companies in Jakarta Islamic Index tend to follow trade-off theory perspective.